Greeting - ., Sociedad Mexicana de Ingeneiria Biomedic (Revista Mexicana de Ingenieria Biomedica, 2018)
Immersed in the emotional impact of the tragedy that has mourned our people, we must dedicate ourselves to the tasks that frame the VIII National Congress.